Irrigation and Greenhouse Gas Emissions: A Review of Field-Based Studies - Sapkota, Anish; Haghverdi, Amir; Avila, Claudia C. E.; Ying, Samantha C. (Soil systems, 2020)
Irrigation practices can greatly influence greenhouse gas (GHG) emissions because of their control on soil microbial activity and substrate supply. However, the effects of different irrigation management practices, such as flood irrigations versus reduced volume methods, including drip and sprinkler irrigation, on GHG emissions are still poorly understood. Therefore, this review was performed to investigate the effects of different irrigation management strategies on the emission of nitrous oxide (N2O), carbon dioxide (CO2), and methane (CH4) by synthesizing existing research that either directly or indirectly examined the effects of at least two irrigation rates on GHG emissions within a single field-based study. Out of thirty-two articles selected for review, reduced irrigation was found to be effective in lowering the rate of CH4 emissions, while flood irrigation had the highest CH4 emission. The rate of CO2 emission increased mostly under low irrigation, and the effect of irrigation strategies on N2O emissions were inconsistent, though a majority of studies reported low N2O emissions in continuously flooded field treatments. The global warming potential (GWP) demonstrated that reduced or water-saving irrigation strategies have the potential to decrease the effect of GHG emissions. In general, GWP was higher for the field that was continuously flooded. The major finding from this review is that optimizing irrigation may help to reduce CH4 emissions and net GWP. However, more field research assessing the effect of varying rates of irrigation on the emission of GHGs from the agricultural field is warranted.